Efektivitas Penyaluran Dana Zakat Infak dan Sedekah pada Badan Amil Zakat Nasional (Periode Tahun 2016-2018) - Elis Nurhasanah (JURNAL EKONOMI SYARIAH, 2021)
Zakah, infaq and Shodaqa are instrument of Islamic social economics having a role in improving the welfare of ummah. The success of this is largely determined by the management of ZIS fund by thr Badan Amil Zakat Nasional. The purpose of this paper is to measure the effectiveness of ZIS fund disbursement by BAZNAS in the period 2016 to 2018. Using quantitative methods with secondary data, namely the financial statements of the audit results of BAZNAS's financial statements during that period, by adopting the calculation of the activity ratio from Puskas BAZNAS. The activity ratio is a measure of the effectiveness of the distribution of zakat, infaq and shodaqa funds. The results showed that BAZNAS during the 2016-2018 period was effective in distributing Zakat funds and was very effective in distributing Infaq shodaqa funds with the Allocation Ratio Zakat and Infaq and Shodaqa ratio of 93% and 106%. The activeness in collecting and distributing ZIS funds is still below 1, it means that the ZIS funds that are collected are not fully channeled during that period or have settled for more than 12 months, so that the ZIS turnover in the BAZNAS institution is said to be still not effective in distributing ZIS funds. Thus the performance of BAZNAS is important to improve so effective in the welfare of the people.